Modified transforaminal epidural steroid injection combined with pulsed radiofrequency: an effective treatment measure for lumbar radiculopathy - Yan, Qi; Zhong, Xianggu; Li, Jiarong; Zhao, Leyu; Niu, Junjie; Song, Dawei; Wang, Jinning; Teng, Yun; Wu, Tianyi; Sun, Xiao; Chen, Rui; Wang, Shuangfei; et al. (Frontiers in Surgery, 2025)
BackgroundLumbar disc herniation (LDH) is a prevalent condition encountered in the clinical diagnosis and management of spinal surgery. Certain people may experience excruciating radicular pain in the lower extremities. If these symptoms are not promptly alleviated, they may progressively deteriorate, ultimately resulting in radiating pain in the lower extremities, advancing neurological impairments, and potential trouble in standing, significantly impairing the patient's quality of life. Consequently, clinicians require an expedited and efficacious approach to address radicular discomfort resulting from lumbar radiculopathy and promptly reinstate the patient's normal functionality.ObjectivesThis study seeks to assess the effectiveness of a modified transforaminal epidural steroid injection (TFESI) in conjunction with pulsed radiofrequency (PRF) for treating lumbar radiculopathy using a retrospective analysis.MethodsOur study examined patients with unilateral lower limb radicular pain persisting for three months or more due to LDH, in whom conservative therapies were ineffective, from January 1, 2023, to October 31, 2023. This trial comprised 106 patients who received modified TFESI alongside PRF. We evaluated clinical efficacy and follow-up at baseline and at 1 week, 1 month, 3 months, 6 months, and 12 months post-surgery primarily using the Visual Analog Scale (VAS), Oswestry disability index (ODI), and modified MacNab score.ResultsPatients who received modified TFESI in conjunction with PRF exhibited substantial enhancements across all three assessment instruments (VAS, ODI, MacNab) when compared to pre-treatment evaluations (p < 0.0001). The alleviation of radicular discomfort was notably enduring, meeting the patients’ expectations. At the 12-month follow-up, we noted that patients often achieved substantial pain alleviation within 6 months, and only a minor proportion of patients encountered pain recurrence by the 12th month, with no notable problems detected.ConclusionsThe modified TFESI in conjunction with PRF is a safe, cost-efficient, and successful therapy modality. Our findings indicated that this method can efficiently and swiftly relieve patients’ radicular discomfort and produce enduring therapeutic effects.